The concise encyclopedia of sociology - Ritzer, George; Ryan, J. Michael (West Sussex : Wiley-Blackwell, 2011)
This concise encyclopedia is the most complete international survey of sociology ever created in one volume.: Contains over 800 entries from the whole breadth of the discipline; Distilled from the highly regarded Blackwell Encyclopedia of Sociology, with entries completely revised and updated to provide succinct and up-to-date coverage of the fundamental topics; Global in scope, both in terms of topics and contributors; Each entry includes references and suggestions for further reading; Cross-referencing allows easy movement around the volume.
Front Matter -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Sociology -- Encyclopedias; Social Science; SOCIAL SCIENCE -- Sociology -- General; Sociology; Soziologie; Electronic books; Encyclopedias